2020
DOI: 10.3390/app10144789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nitrogen and Phosphorus Removal from a Denitrifying Woodchip Bioreactor Treatment System Receiving Silage Bunker Runoff

Abstract: Leachate and storm-driven runoff from silage storage bunkers can degrade receiving water bodies if left untreated. This study evaluated a novel treatment system consisting of three treatment tanks with a moving-bed biofilm reactor and paired side-by-side denitrifying woodchip bioreactors for the ability to reduce influent nutrient mass loads. Flow-based samples were taken at four locations throughout the system, at the inflow to the first tank, outflow from the tanks prior to entering the woodchip bioreactors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A bioreactor is a vessel that contains a biologically active environment, typically with a mix of bacteria, fungi, and other microorganisms. Bioreactors can be used to remove contaminants from water by encouraging the growth of microorganisms that break down the pollutants (Sarazen, 2020, Valenca et al, 2021. The type of bioreactor used depends on the specific contaminants that need to be removed.…”
Section: Use Of Natural Treatment Systems Of Greenmentioning
confidence: 99%
“…A bioreactor is a vessel that contains a biologically active environment, typically with a mix of bacteria, fungi, and other microorganisms. Bioreactors can be used to remove contaminants from water by encouraging the growth of microorganisms that break down the pollutants (Sarazen, 2020, Valenca et al, 2021. The type of bioreactor used depends on the specific contaminants that need to be removed.…”
Section: Use Of Natural Treatment Systems Of Greenmentioning
confidence: 99%
“…Total P reduction was 84% [12]. More recently, Sarazen et al [88] evaluated a novel treatment system consisting of three treatment tanks with a moving-bed biofilm reactor and paired denitrifying woodchip bioreactors. The system's performance was monitored during 16 storm events throughout 2019.…”
Section: Omrmentioning
confidence: 99%
“…Ateia et al (2015) investigated the effect of salinity on the MBBR performance to remove COD from agricultural drainage water and concluded that after the proper acclimation of the system to salt levels below 7.5 g/L, the effluent reached the quality standards for reuse in agricultural purposes. Sarazen et al (2020) reported the use of an aerated MBBR followed by a denitrifying woodchip bioreactor for the treatment of leachate and storm-driven runoff from silage storage bunkers, reaching a reduction of Total Nitrogen mass load by 76% and only 26% of the Total Phosphorus mass load. They also recommend this system as a promising solution for situations where N is already in the form of nitrate.…”
Section: Introductionmentioning
confidence: 99%